PROFIL KUMAN PADA SEKRET HIDUNG PENDERITA RINOSINUSITIS KRONIS DI RUMAH SAKIT HAJI MEDAN - Harahap, Nahda Ismi Karunia; Siregar, Siti Masliana; Nasution, Muhammad Edy Syahputra (JURNAL IBNU SINA BIOMEDIKA, 2018)
Introduction: Rhinosinusitis is an inflammation of the paranasal sinus mucosa. Rhinosinusitis is a disease commonly found in daily physician pratice as well as one of the most common of health worldwide. Rhinosinusitis causes a high economic burden and a considerable decreased in quality of life, decreased productivity and also concentration in work. Chronic rhinosinusitis is a inflammatory process of the mucosa due to infection and lasted more than 3 months. Change in pattern of bacteria and fungi are thought to affect the increase the prevalence of chronic rhinosinusitis. Methods: Descriptive study was cross-sectional study of the patterns of microorganism in patients with chronic rhinosinusitis in RSU Haji Medan. Sample was taken by a funtional endoscopic sinus surgery and then cultur in medium. Results: from 26 patients, found 57,7% male, 42,3% female. Age group 0-20 years 7,7%, 21-40 years 65,4% and >40 yeras 26,9%. Type of maxillaris sinusitis 42,3%, multisinusitis 30,8% and pansinusitis 26,9%. Symptomp of nasal obstruction 50%, headache 34,6%, smelling nose 3,9% and facial pain 11,5%. The most bacterial is Staphylococcus aureus 34,6% and than Proteus sp 23,1% and the least are Staphylococcus albus and Staphylococcus sp 7,7%. The most fungal is Candida sp 42,3%. Conclusion: the mostmicroorganisms pattern in patients with chronic rhinosinusitis in RSU Haji Medan September-Desember 2017 is Staphylococcus aureus and Candida sp.Key word : bacterial, chronic,FESS, fungal,rhinosinusitis Â